Preparing Graduates for the Workforce: The Development of Contextual-Based History Learning E-Modules in Vocational Schools - Nur Aeni Marta; Abdurakhman Abdurakhman; Djunaidi Djunaidi (History Department, Semarang State University and Historian Society of Indonesia, 2023)
During the COVID-19 pandemic, history lessons were carried out online. As a result, several obstacles are encountered, including internet network problems. Teachers have difficulty carrying out learning activities in class optimally and meaningfully. Meanwhile, there has been no contextual-based history e-module for Vocational High Schools. Even though history learning for SMK should be different from SMA. The direction and objectives of SMK learning are to strengthen graduate competency standards to be ready for work. For this reason, researchers recommend using contextually based e-modules as an effort to prepare graduates who are ready to work. Contextual e-modules are modules that are presented electronically; the material is related to other subject matter that is relevant to the field of vocational science and graduate competency achievements. The research used the RD method with the ADDIE approach. The results of the study show that contextually based E-modules can optimize history learning and encourage innovative creativity. The advantages of contextually based E-modules are that the material is related to areas of expertise, easily accessible at any time, and can be studied independently and repeatedly. As a result, learning history can be carried out effectively and thoroughly.Pada masa pandemi COVID-19, pembelajaran sejarah dilakukan secara daring. Dampaknya, terdapat beberapa kendala yang dihadapi di antaranya adalah masalah jaringan internet. Guru mengalami kesulitan melaksanakan kegiatan pembelajaran di kelas secara optimal dan bermakna. Sementara itu, selama ini belum ada e-modul sejarah berbasis kontekstual untuk SMK. Padahal seharusnya pembelajaran sejarah untuk SMK berbeda dengan SMA. Arah dan tujuan pembelajaran SMK adalah memperkuat standar kompetensi lulusan untuk siap kerja. Untuk itu, peneliti merekomendasikan penggunaan e-modul berbasis kontekstual sebagai upaya mempersiapkan lulusan yang siap kerja. E-modul berbasis kontekstual merupakan modul yang disajikan melalui elektronik, materi dikaitkan dengan materi pelajaran lain yang relevan dengan bidang ilmu kejuruan dan capaian kompetensi lulusan. Penelitian menggunakan metode RD dengan pendekatan ADDIE. Hasil penelitian menunjukkan E-modul berbasis kontekstual dapat mengoptimalkan pembelajaran sejarah dan mendorong muncul kretivitas inovasi baru. Kelebihan E-modul berbasis kontekstual adalah materi dikaitkan dengan bidang keahlian, mudah diakses kapan saja, serta dapat dipelajari secara mandiri, dan berulang-ulang. Dampaknya, pembelajaran sejarah dapat dilakukan secara efektif dan tuntas.